Socio-Occupational and Physical Outcomes More than 20 Years after Diagnosis for Osteosarcoma in Children and Adolescents: Limb Salvage versus Amputation - Ottaviani, Giulia (2013)
BACKGROUND: To date, there has been relatively little research on very-long-term survivors of childhood and adolescent osteosarcoma. We sought to compare the very-long-term outcomes of osteosarcoma patients treated with either limb salvage procedures or amputation. MATERIALS AND METHODS: Thirty-eight long-term osteosarcoma patients surviving 20 or more years from diagnosis were divided into two groups according to whether they underwent amputation or limb salvage. Participants were asked to complete a questionnaire about education, employment, annual income, marital status, health insurance, lifestyle, siblings, and all current and past health issues. RESULTS: Education, employment, marital status, and health insurance did not differ significantly between the two groups of survivors, and they described themselves as similar to their siblings. Eight percent of survivors underwent secondary amputation due to complications with an endoprosthesis. The cumulative incidence of second primary neoplasms was 13%, and this was significantly higher in females and in survivors who underwent radiotherapy and had genetic predisposition. The second primary malignancies were breast cancer (ductal invasive carcinoma, ductal in situ carcinoma, leiomyosarcoma), mediastinal leiomyosarcoma, squamocellular carcinoma of the oral cavity and of the uterine cervix. Amputees required more assistive walking support than survivors who received limb salvage treatments (χ(2) test, p <0.05). CONCLUSIONS: Despite the many challenges that osteosarcoma survivors face, patients who survived over 20 years after their initial diagnosis reported having overall adjusted well to their physical limitations and were productive individuals.